A Jack of All Trades: Impact of Glucocorticoids on Cellular Cross-Talk in Osteoimmunology - Ahmad, Mubashir; Hachemi, Yasmine; Paxian, Kevin; Mengele, Florian; Koenen, Mascha; Tuckermann, Jan (Frontiers in Immunology, 2019)
Glucocorticoids (GCs) are known to have a strong impact on the immune system, metabolism and bone homeostasis. While these functions have been long investigated separately in immunology, metabolism, or bone biology, the understanding of how GCs regulate the cellular cross-talk between innate immune cells, mesenchymal cells and other stromal cells has been garnering attention rather recently. Here we review the recent findings of GC action in osteoporosis, inflammatory bone diseases (rheumatoid and osteoarthritis) and bone regeneration during fracture healing. We focus on studies of pre-clinical animal models that enable dissecting the role of GC actions in innate immune cells, stromal cells and bone cells using conditional and function-selective mutant mice of the GC receptor (GR), or mice with impaired GC signaling. Importantly, GCs do not only directly affect cellular functions, but also influence the cross-talk between mesenchymal and immune cells, contributing to both beneficial and adverse effects of GCs. Given the importance of endogenous GCs as stress hormones and the wide prescription of pharmaceutical GCs, an improved understanding of GC action is decisive for tackling inflammatory bone diseases, osteoporosis and aging.